Pixel mapping method (PMM) based bit plane complexity segmentation (BPCS) steganography - Bhattacharyya, S.; Khan, A.; Nandi, A.; Dasmalakar, A.; Roy, S.; Sanyal, G. (2011 World Congress on Information and Communication Technologies, 2011)
Steganography is the art and science of communicating in a way which hides the existence of the communication. Important information is firstly hidden in a host data, such as digital image, text, video or audio, etc, and then transmitted secretly to the receiver. In this work the authors propose a new image based steganographic method for hiding information within the spatial domain of the gray scale image. The proposed method is based on pixel mapping method(PMM) for image data and bit-plane complexity segmentation (BPCS) steganography. The proposed approach works by selecting the embedding bit planes using some mathematical function and then applies the pixel mapping method (PMM) in a 8×8 blocks of the each selected plane. The integrated approach of PMM and BPCS produces a robust image based steganography method which is independent of the nature of the data to be hidden and produces a stego image with minimum degradation. The experimental results shows this method is sperior to other existing methods in terms of robustness and embedding capacity tradeoffs.